“It takes a lot of sisu to get through it”- managerial experiences of facing adversities during pandemic - Johanna Vuori; Ilmari Määttänen (International Journal of Qualitative Studies on Health & Well-Being)
Purpose Sisu refers to extraordinary internal strength in the face of adversities. Although originally a Finnish concept, it can be a universally useful concept for studying managerial well-being and performance during difficult or even emergency periods. Previous research on sisu categorizes it into beneficial and harmful sisu and suggests that these two dimensions of sisu are useful when studying determination and resoluteness in crisis situations. This study applies the concept of sisu to examine managers’ well-being in times of crisis. Methodology Interviews were conducted with 15 managers in the hotel, manufacturing and retail industries in Finland. Results The beneficial effects of sisu seem to dissolve when it is used too often. The study also highlighted the paradoxical tension involved in the decision to stop or continue actions in a difficult situation and contributes to sisu research by discussing collective sisu. Conclusion The results of this study suggest that beneficial sisu helps to overcome adversity, while harmful sisu causes distortions in thinking that are detrimental to managers. Understanding one’s own tendency towards beneficial or harmful sisu in difficult situations can help in managerial work. Collective sisu is an excellent resource for overcoming difficult situations in workplaces.